Morfoanatomia e histoquímica comparativa entre Alternanthera brasiliana (L.) Kuntze e Alternanthera dentata (Moench) Stuchlik; estudo fitoquímico e biológico de Alternanthera brasiliana - Pereira, Danielle Fontana (2007)
The family Amaranthaceae consist of approximately 65 genus and 1000 species of herbaceous plants. The genus Alternanthera is in this family and can be found spread worldwide. The Alternanthera brasiliana (L.) Kuntze and Alternanthera dentata (Moench) Stuchlik species are known as penicillin and can be found in Brazil, commonly in Santa Catarina and Rio Grande do Sul. The popular usage of the A. brasiliana specie is for the treatment of tonsillitis, cold and the influenza and the A. dentata is used to treat infections, fever along with headache and is also used as antiseptical for the treatment of itches and wounds. This work aims at to stipulate pharmacognostics parameters of distinguishment between the two cited species because there is a disagreement among the botanics about the existence of the dentata species. The macroscopical characteristics that can help authenticate them are: the perimeter, color, the abundance of trichomas in the limb and the shape of the stalk. The anatomical analysis had allowed the distinction through the type of found stomata (anfiestomatic and hipostomatic), the existence of the collenchyma disposal of the phloem and the absence of trichomes in the adaxial surface of A. dentata. The presence of the Kranz sheath characterized the type C4 of the Amaranthaceae family. Additionally, this work describes the identification of β-sitosterol, stigmasterol and espinasterol isolated from dichloromethane fraction of A. brasiliana leaves. The A. brasiliana leaves used in the pharmacobotanic and phytochemistry analyses and in the biological activities were collected in December 2004 and March 2005 in Santa Cruz do Sul (RS) and Santa Maria (RS), the leaves were identified by the biologist Dr. Thaís do Canto Dorow (Dpt. of Biology, UFSM). The vouchers are deposited in the Department of Biology herbarium of UFSM respectively under the register numbers SMDB 10038 and 10039. The A. dentata specie used in the morphoanatomic study was collected in Florianópolis (SC) and was identified by the researcher Antônio Amaury Silva Jr. of EPAGRI-SC and confirmed by Elen N. Garcia and Sílvia Rubin, both biologists of the Federal University of Pelotas. This specie used in the study is registered in the institution 03 herbarium (PEL-UFPEL) 04/07/06 and in the UFSM herbarium SMDB 10100. In relation to the antimicrobial activity the best result was obtained in the dichloromethane fraction with the Prototheca zopffi algae but it was also found satisfactory MIC for the Gram-positive S. aureus and B. subtillis bacteria and for the S. cerevisiae fungus. The biggest antioxidant activity was found in the acetate of ethyla fraction wich evidenced a IC50=163, 01ug/mL. The correlation between the polyphenol tenors and the antioxidant activity was not possible.